Heterogeneity of symptomatology in socially anxious adolescents: are case conceptualizations based on perceived causal networks (PECAN) able to capture personalized symptoms and their relations? - Vogel, Felix; Delvert, Alice; Rupp, Sophie; Reichert, Julian (Cognitive therapy and research, 2025)
Social anxiety disorder (SAD) is a prevalent and challenging mental disorder in children and adolescents, with traditional cognitive models often failing to account for its heterogeneity. This study explores personalized symptom networks based on individuals’ perception as an alternative approach.
Gesehen am 30.01.2026